Rickettsial fever in tertiary care hospital in rural Bengaluru: Clinical profile and complications - Saravanan, P; Nagaraj, M V; Somashekhar, C (Indian Journal of Child Health, 2020)
Background: Rickettsial fever is a major health concern in different districts of Karnataka with serious complications, including morbidity and mortality, if diagnosed late. Objective: The objective of the present study was to know the clinical profile of Rickettsial fever in children. Materials and Methods: A descriptive study was conducted on all the laboratory-confirmed cases of Rickettsial fever in children admitted to a tertiary care hospital from December 2018 to November 2019. Results: Among 103 children studied, majority were males (66%) in the age group of 3–6 years. All the children presented with history of fever (100%) followed by decreased appetite (94%). The least common symptoms noticed were altered sensorium (1.9%), breathlessness (6.5%), and bleeding tendencies (6.5%). The most serious complications seen were shock (38.8%), hepatic dysfunction (7.7%), and myocarditis (3%). There were no deaths reported. The least common complication was renal failure. A single case had cranial nerve palsy with meningitis. Conclusion: It was concluded that male children in the age group of 3–6 years were more affected. The common symptoms observed were fever, decreased appetite, abdominal distension, and skin rash and the common complications were shock and myocarditis.